Body image of men and women with congenital heart disease over a 15 years observational period - Siegfried Geyer; Claudia Dellas; Elmar Brähler; Johannes Beller (Scientific Reports)
Abstract Most studies devoted to the psychological consequences of congenital heart disease (CHD) have dealt with consequences in terms of psychopathology. We wanted to consider two specific aspects of body image, “Rejecting body evaluation” and “Vital body dynamics”. We examined body image of CHD-patients as compared with the general population, the stability of body image of patients over time, and the relationship of body image with disease severity. The study combined a longitudinal (panel-) and a case-control design. The findings were based on a long-term study of CHD-patients with two surveys about 15 years apart with N = 244 who participated in both. The control group consisted of the same number of cases matched by age, gender and education drawn from a national survey designed to examine body image in the general population. More men than women were classified into the group with severe CHD. Body image differences between CHD-patients and controls were found only in men, but not in women, and they emerged primarily in terms of vitality. The two dimensions of body image turned out as moderately to strongly stable over time, relationships between disease severity and body image emerged only for perceived vitality. Contrary to expectation, effects of age and sex were largely absent. The body image of men turned out to be more affected by congenital heart disease than women. Body image is not stable, but it is changing with increasing age, and disease severity is affecting body image only in terms of the perception of physical performance.